Endovascular or open surgical management for inadvertent cannulation of vertebral artery during central venous cannulation? - RPS. Gambhir; M Garg; O Hargrove; Baldwin Melissa; N Kandasamy (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Inadvertent cannulation of vertebral artery while attempting to insert a central venous cannula in the internal jugular vein is a very rare complication and can occur inspite of use of ultrasound guidance. This case report discusses the management of vertebral artery cannulation in a 56 year old lady electively admitted for hepatectomy. Once recognised, rather than catheter removal and external compression which can be fatal, an immediate multidisciplinary discussion must make the choice between endovascular intervention or open repair, each intervention carries its risks. In our case it was managed successfully by open surgical approach.